Zadovoljstvo zdravstveno negovalnega osebja v zdravstveni negi in oskrbi v Domu upokojencev Idrija - Kobal, Klavdija (Obzornik zdravstvene nege, 2006)
The aim of the article is to shed light on the satisfaction of the employees in nursing care and provide. The introduction presents the factors of satisfaction, as well as the stress factors which can be an indirect cause of weariness at the workplace. On the basis of the surveys results carried out among the employees in nursing care and provide in the retirement home Dom upokojencev Jožeta Primožiča Miklavža in Idrija, the author establishes that the employees are satisfied with the work they do. The results analysis have shown that additional stress at the workplace reduces the satisfaction of the employees. Employees feel overburdened. Even though they are satisfied with their workplace, the majority of the employees would decide to change their job had they the opportunity to do so. The employees in nursing health care inthe retirement home Dom upokojencev Idrija cannot imagine being able to carry out their current job until retirement. The thesis that the employees would be most motivated by a higher salary has turned out to be incorrect, since the majority of the employees believe that the best motivation for them would be more annual holidays.
Keywords: zadovoljstvo; zdravstvena nega; zdravstveni delavci